Distortion Of Printed Resin Surgical Guides After Autoclave Sterilization And Chemical Disinfection - Natasha Gandarilla, DMD (Elsevier, 2024)
OBJECTIVES: To examine the level of distortion of 3D printed surgical guides after steam sterilization and disinfection by immersion in 70% isopropyl alcohol. The results will provide a basis for developing a protocol for the sterilization of surgical guides. METHODS: A maxillary stone model was scanned with Prime Scan optical scanner (Dentsply Sirona, Charlotte, NC) and the standard tessellation language (STL) file of the model was exported and uploaded to Blue Sky Bio® software. The model was modified to extract tooth #8 digitally in the Blue Sky Bio® software. Surgical guides were designed to extend from tooth number 6 to 10. Forty guides were printed with Formlabs Form 3B+ printer and Formlabs surgical guide resin following manufacturer's instructions. Each guide was scanned with Prime Scan optical scanner before disinfection and sterilization. Twenty guides were individually packaged, and autoclave sterilized at manufacturer's recommendation of 134°C for 20 minutes. The remaining twenty guides were soaked in 70% isopropyl alcohol for fifteen minutes. After sterilization and disinfection, the guides were scanned and STL files from pre- and post-sterilization were compared in GeoMagic Control X software to examine dimensional changes. A paired T-test was done to evaluate distortion of the guide before and after sterilization and disinfection. An unpaired T-test was done to compare the disinfection and sterilization test groups. RESULTS: The average deviation at the lingual, incisal, buccal, combined surfaces, and the entire guide of the sterilized group was 6.28μm, -2.4μm, -20.6μm, 5.6μm, and 12.6μm respectively. The average deviation at the lingual, incisal, buccal, combined surfaces and the entire guide of the chemically disinfected group was -0.43μm, 2.6μm, -0.78μm, 0. μm, and 5.5μm respectively. Paired T-test of the sterilized group showed a significant difference before and after sterilization at all surfaces with p-values <0.05. Paired Ttest of the disinfection group showed no significant difference before and after chemical disinfection at any surface. Unpaired T-test between the sterilized and disinfected group showed a non-significant difference between the incisal and total averages. There was a statistically significant difference between the average deviation of the lingual surfaces with a p-value of 6.31763E-06, the buccal surface with a pvalue of 3.83055E-13, and the combined surfaces with a p-value of .0001. CONCLUSIONS: Results indicate that there is distortion after sterilization and minimal distortion with chemical disinfection. However, the amount of distortion will likely not cause a clinically significant effect on the seating of the surgical guides. This is an indication that surgical guides can be either sterilized or disinfected prior to implant placement. IMPLICATIONS: The results will provide a basis for developing a protocol for the sterilization of surgical guides.